Building Resilience in Sandwich-Generation Families: Financial Literacy and Emergency Fund Ownership from an Islamic Socio-Cultural Perspective - Irni Rahmayani Johan; Sifa Nabila Azzahra; Megawati Simanjuntak; Mohamad Fazli Sabri (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2025)
Families in the sandwich-generation shoulder responsibilities for children and elderly parents, creating significant financial strain. This study examines how demographic characteristics and financial literacy, encompassing knowledge, attitudes, and behaviour, affect emergency fund ownership among sixty sandwich-generation households in Bogor Regency, Indonesia. Data were collected through structured interviews and supported by several in-depth interviews to capture socio-cultural context. Descriptive statistics, Spearman/Kendal tau-b correlation, and logistic regression were employed in the analysis. The findings indicate that most respondents demonstrated low financial knowledge and poor financial behaviour, though their financial attitudes were moderately positive. More than half of the families lacked adequate emergency savings, with higher income significantly improving the likelihood of ownership, while a greater number of children reduced it. Importantly, financial knowledge emerged as a positive and significant predictor of emergency fund ownership. Beyond economic implications, the results highlight the socio-religious dimension of family resilience. In Islamic tradition, safeguarding wealth (ḥifẓ al-māl) and fulfilling intergenerational obligations reflect both moral duty and social solidarity. Thus, strengthening financial literacy not only enhances economic security but also aligns with Islamic values of prudence, responsibility, and care for family members. Integrating these insights contributes to a deeper socio-cultural understanding of resilience within Muslim families.